Role of hospital pharmacists in reporting adverse drug reactions - A review - Sharmila P Nirojini; Rama Rao Nadendla; Valli B Manalan; Habeeb AR Ibrahim (Archives of Global Professionals, 2012)
Adverse drug reactions (ADRs) are one of the leading causes of morbidity and mortality. ADRs account for about 5% of the hospital admissions, though 60% of the ADRs are preventable. Being a medicine expert, the pharmacists in the hospital sectors can play a significant role in detecting, monitoring, and reporting ADRs. With sound knowledge on drug therapy and disease management, they are the preferred group of professionals in ensuring drug and patient safety. Underreporting of ADRs is a serious problem; and the possible reasons for that include the lack of awareness among healthcare professionals and inadequate patient education. There is a need for proper training to hospital pharmacists on ADR reporting. Implementing good pharmacovigilance (PV) practice in the hospital settings can lead to proper reporting of ADRs. This manuscript reviews the published literature on the consequences and under-reporting of ADRs, importance of PV, and the hospital pharmacists' contributions in drug and patient safety.